Study of Phytochemical Constituent and Biological Activities of Methanolic Extract of Rhizomes of Neopicrorhiza scrophulariiflora and Roots of Rheum australe collected from the Alpine Region of Nepal - Kumai, Ganesh Prasad; Baskota, Manish; Aryal, Pramod; Subba, Bimala (Journal of Nepal Chemical Society, 2023)
Rhizomes of Neopicrorhiza scrophularii flora and roots of Rheum australe were collected from the alpine regions of the Jumla district of Nepal. The phytochemical analysis of the methanolic extract of these plants revealed the presence of polyphenols, flavonoids, quinones, saponins, and tannins. The total phenolic and flavonoid content in the extracts of N. scrophulariiflora were estimated to be 141.27±1.414 mg GAE/gm and 43.48±5.476 QE/gm respectively and that in the extracts of R. austral were estimated to be 101.54±4.061 mg GAE/gm and 24.97±2.857 mg QE/gm respectively. A brine shrimp lethality test was performed with the extracts of N. scrophulariiflora and R. austral against brine shrimp nauplii and results revealed high toxicity of the extracts towards nauplii with LC50 values 173.78μg/mL and 257.03μg/mL respectively. N. scrophulariiflora showed the strongest DPPH radical scavenging activity with IC50 value of 57.49 μg/mL in comparison to R. austral whose IC50 was determined to be 68.91μg/mL, ascorbic acid taken as standard with IC50 value 49.05μg/ml. In α-amylase inhibition assay, N. scrophulariiflora extract exhibited strong activity with IC50 value 140.67μg/mL while that of R. austral extract showed mild activity with IC50 value 192.88μg/mL. All the biological studies revealed that N. scrophulariiflora extract is more active than that R. austral extract. Column chromatography of the extract of N. scrophulariiflora was performed and 50 % methanolic fraction was further subjected to FTIR and GC-MS analysis. The GC-MS analysis showed various compounds and among them, 13 major compounds were identified.